An integrated superconducting phase switch for cosmology instruments - Yassin, G; Kuzmin, L; Grimes, P; Tarasov, M; Otto, E; Mauskopf, P (2007)
We present the design of a low loss planar phase switch operating at millimetre and submillimetre wavelengths. The system comprises a superconducting nanostrip that switches the RF signal between the two branches of a microstrip phase circuit. The employment of superconducting components reduces conduction losses to a negligible level. The required cooling below the transition temperature does not add extra effort since all high performance detectors employ superconducting circuits, and are in fact cooled well below the transition temperature of the phase circuit material. The proposed fully planar design allows the switch to be easily integrated into the detector circuit and eventually the realisation of a fully planar receiver. This avoids the use of bulky, expensive and lossy waveguide components and allows the fabrication of reliable and cheaply mass producible polarimeters that are now routinely used in large format CMB arrays. © 2007 Elsevier B.V. All rights reserved.